Pengaruh Promosi Kesehatan Melalui Buku Praktis Kesehatan Ibu Hamil Preeklamsia Terhadap Pengetahuan Kader Kesehatan - Ulty Desmarnita; Yuli Mulyanti (Jurnal Keperawatan, 2019)
Hypertension during pregnancy may lead to a serious condition called preeclampsia.Health cadre should be provided with information concerning identification of such risk. This study aimed to identify the impact of guidebook of pregnant woman with preeclampsia on knowledge and attitude in pregnant women in health cadre. The study design was quasi-experimental withnon-randomized pretest-posttest group control approach. This study involved 60 health cadres whom were assigned into two groups, intervention group (n= 30) and control group (n= 30) and recruited through purposive sampling technique. The results suggest that there was significant difference in health cadre’s attitude between both groups (p= 0.000). Variable of duration being a cadre is the most determinant factor affecting cadre’s attitude. Health promotion through guidebook of pregnant woman with preeclampsia was effective in improving health cadre’s attitude. Authors recommend health cadres to use the guidebook of pregnant woman with preeclampsia when enacting their duties.